Evaluating the feasibility of Managed Aquifer Recharge techniques as a drought mitigation strategy for the Seville water supply system (southern Spain) - Ávila-Marín, José María; Gil-Márquez, José Manuel; Andreo-Navarro, Bartolomé (Elsevier, 2025)
Managed Aquifer Recharge (MAR) is a recognised strategy for improving water security, particularly in regions facing increasing droughts and water demand due to climate change. However, gaps remain in assessing MAR feasibility through drought analysis, pilot testing, and resource availability evaluation. This study details a MAR pilot project in the Guillena-Cantillana Groundwater Body (GWB), part of the Niebla-Posadas aquifer, Seville, Spain, via storing released reservoir water for abstraction during dry episodes to evaluate its potential for mitigating supply system drought impacts. A hydroclimatic study using statistical analysis of the Standardised Precipitation Evapotranspiration Index (SPEI) revealed increasing drought trends and favourable wet periods for MAR implementation. The analysis of historical droughts and SPEI provided key insights into the duration of recharge and extraction periods, while trend analysis helped assess the long-term availability of water resources for MAR. The pilot test involved direct gravity injection of 4183 m3 of surface water, with monitoring of water levels, electrical conductivity, pH, and concentrations of ions and metals to assess hydrodynamic and hydrochemical responses and provided data on recharge and abstraction rates. Results confirm that MAR via wells is technically and environmentally feasible in the study area, with no adverse effects on groundwater quality and sufficient aquifer recharge capacity. Hydrogeochemical modelling provided insights into recharge-groundwater interactions. This study highlights the value of hydroclimatic trend analysis, drought indices and pilot testing in MAR planning, demonstrating its potential to enhance Seville's water resilience and offer a transferable framework for similar confined aquifers worldwide.
Keywords: Aguas subterráneas - Alimentación artificial; Aguas subterráneas - Gestión; Sequía - Sevilla; Managed aquifer recharge; Seville, Spain; SPEI-12; Integrated water management; Drought-adaptation strategy